PROFITABILITY AND FINANCIAL DECISIONS ON FIRM VALUE: MODERATING ROLE OF FIRM SIZE - Saputra, Devina; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2025)
This study explores the connection between profitability, financial decisions, and firm value, with firm size acting as a moderating variable. It focuses on industrial sector companies listed on IDX 2021-2023, employing multiple regression analysis. The findings reveal that profitability has a significant positive impact on firm value, implying that greater profitability leads to an increase in firm value. Similarly, financial decisions positively influence firm value, indicating that effective debt utilization can enhance a company's value. While firm size does not moderate the relationship between profitability and firm value, it does strengthen the impact of financial decisions on firm value, suggesting that larger firms are more responsive to financial decisions.This research provides important insights into strategic financial management in enhancing firm value in Indonesia's industrial sector.